High Intracellular Seed Train BiP Levels Correlate With Poor Production Culture Performance in CHO Cells. Issue 10 (24th April 2018) - Tung, Meg; Tang, Danming; Wang, Szu‐Han; Zhan, Dejin; Kiplinger, Karen; Pan, Shu; Jing, Yifeng; Shen, Amy; Ahyow, Patrick; Snedecor, Brad; Gawlitzek, Martin; Misaghi, Shahram
Abstract : Consistent cell culture performance is a prerequisite to ensure product quality consistency and achieve productivity goals for the manufacture of recombinant protein therapeutics, including monoclonal antibodies. Here a peculiar observation is reported where high levels of intracellular BiP in seed train cultures are consistently predictive of poor cell culture performance in the subsequent inoculum and production cultures for a monoclonal antibody produced in CHO cells. This investigation suggests that in this cell line the high intracellular BiP levels in the seed train are triggered by a slightly lower culture pH, which interferes with proper antibody folding and secretion. While the seed train culture does not display any obvious signs of the problem at slightly lower culture pH, inoculum trains, and production cultures sourced from these low pH seed trains display significantly lower cell growth and cell size. High intracellular BiP levels may interfere with UPR signaling, thereby hampering a proper and timely UPR response in the production media. Studies of other problematic cell lines have shown a similar correlation between intracellular BiP accumulation and poor production performance. The authors believe intracellular BiP levels in seed train should hence be low in order to increase the success rate in production. Abstract : In the case of a mAb X cell line, inefficient antibody folding and secretion at low pH (7.05) triggers higher intracellular BiP levels. Accumulation of intracellular BiP in seed train culture may interfere with proper UPR response when cells are cultured in the rich production media, leading to inability of cells to cope with the increased production demands, which may further cause lower titers and lower growth compared to the expected runs.